Comfortably Numb: A Short History of New Zealand Muslim Discourse and Thought (American Journal of Islam and Society, 2021)
This article intends to sketch a history of some of the principle ideas, themes and values buttressing New Zealand Muslim thought and Weltanschauung. The argument is predicated upon the hypothesis that in defining religious and spiritual identity one of the most vital aspects to be taken into consideration are the multiple differences in epistemological, methodological and ontological assumptions as we try to comprehend the primary sources of religious knowledge and practice. In the first section of the article, the general heuristic and methodology of describing and demarcating the identities of Muslims, or ways of being a Muslim in New Zealand, in an existential sense, is presented. The second part discusses research that has detected and delineated Muslim identity among New Zealand citizens. The third section attempts to present an elucidation on some of the main topics underpinning the worldview of local Muslims, including the precepts of religio-communal authority, autonomy and agency, and ideas related to the conceptualisation and interpretation Islamic traditions.